HUBUNGAN POWER OTOT LENGAN DAN BAHU DAN KOORDINASI MATA TANGAN DENGAN KETEPATAN HASIL SERVIS ATAS PERMAINAN BOLA VOLI PADA TIM PUTRI SMK NEGERI 1 PEKANBARU (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: The problem in this research is the ability of the service above is still less than the maximum. Viewed from a still often fail in performing the service over a less harsh, sharp, and purposeful. Errors that often occur when servicing is throw up. Like too far forward so that the ball will be caught in the net, too far to the rear so that the ball will be out of the field, on the throw the back of the head so that the service loss of strength. Too far in front of the head so that it will reduce the strength of the service. The purpose of this study was to determine whether there is relantionship of power of arm muscles and shoulder and hand eye coordination to the accuracy of the results of the service over a game of volleyball on the women’s team of SMK Negeri 1 pekanbaru. The population in this research is all the women’s volleyball team smk negeri 1 pekanbaru totaling 12 people.sampling techniques that entire population. This research use test of two hand medicine ball put, fetch a tennis ball, and the accuracy of service over. The results of this test that there is a relationship of power muscle arm and shoulder with the accuracy of the results of the service over a game of volleyball with a correlation rx1y= 0,047 with the level of relationship very low. there is a relationship hand eye coordination to the accuracy of the results of the service over a game of volleyball with a correlation rx2y= 0,333 with the level of relationship low. there is a relationship of power muscle arm and shoulder and hand eye coordination to the accuracy of the results of the service over a game of volleyball with a correlation rx1x2y= 0,110 with the level of relationship very low. Keywords : Power muscle arm and shoulder, hand eye coordination, the accuracy of service over.